Herbage accumulation and grazing losses on Mulato grass subjected to strategies of rotational stocking management (Scientia Agricola, 2013)
Grazing management strategies affect not only herbage accumulation but also the efficiency of grazing. This study aimed to evaluate herbage accumulation (leaf, stem and dead material), grazing efficiency and losses of mulato grass (a Brachiaria ruziziensis × Brachiaria brizantha cv. Marandu hybrid) subjected to strategies of rotational stocking management. Treatments consisted of combinations between two post-grazing heights (15 and 20 cm) and two pre-grazing conditions (95 % and maximum canopy light interception (LI)) assigned to experimental units (1200-m² paddocks) according to a 2 × 2 factorial arrangement and a randomized complete block design, with four replications. The experiment was carried out from Jan 2008 to Mar 2009. Season of the year influenced almost all studied variables, resulting in a common pattern of response that was determined by pre- and post-grazing management targets. Herbage accumulation was greater on swards managed at 95 %, with higher accumulation of leaves and lower accumulation of stem and dead material in relation to those managed at maximum LI (99 %) during the entire experimental period. On the other hand, herbage removal by grazing was larger on swards managed at 99 % LI, which was compensated for by the smaller number of grazing cycles and larger losses due to grazing under those circumstances. Under rotational stocking, the pre-grazing LI of 95 % and post-grazing height of 20 cm resulted in efficient grazing and high producing leafy pastures, highlighting the potential of Mulato grass pastures for animal production.